2016
DOI: 10.3928/01477447-20160129-06
|View full text |Cite
|
Sign up to set email alerts
|

Transosseous Physeal-Sparing Rotator Cuff Repair in an Adolescent Football Player

Abstract: Rotator cuff injuries in the pediatric and adolescent population are rare. These injuries are normally caused by an acute event or by repeated microtrauma as a result of poor mechanics during overhead sporting activities. Overall, these injuries account for fewer than 1% of all rotator cuff tears. Physeal injuries, tuberosity avulsions ("rotator cuff equivalents"), and proximal humeral fractures commonly occur in the pediatric population. Traumatic full-thickness rotator cuff ruptures that occur in this age gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(27 citation statements)
references
References 17 publications
1
26
0
Order By: Relevance
“…Pediatric rotator cuff repair should be approached using a physeal-sparing technique to avoid potential growth disturbances. Although the literature is sparse, previously described techniques underemphasize physeal-sparing techniques and use an open approach 2, 6. Our technique highlights an arthroscopic approach with fluoroscopic confirmation of preservation of the physis.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pediatric rotator cuff repair should be approached using a physeal-sparing technique to avoid potential growth disturbances. Although the literature is sparse, previously described techniques underemphasize physeal-sparing techniques and use an open approach 2, 6. Our technique highlights an arthroscopic approach with fluoroscopic confirmation of preservation of the physis.…”
Section: Discussionmentioning
confidence: 99%
“…Contusions to the rotator cuff are reported in contact athletes and can present with a short-term loss of muscle strength and function 3 . Fortunately, traumatic rotator cuff tears in this population are rare, and the literature contains predominantly case reports and small series without attention to physeal-sparing repair techniques 2, 4, 5, 6, 7…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rotator cuff (RC) tears are common injuries sustained by competitive overhead athletes resulting from acute trauma or more commonly, chronic degenerative changes from overuse. 1,2 These injuries have been frequently documented in both collegiate and professional level athletes in which a repetitive overhead throwing motion is used. [3][4][5] When RC tears occur in athletes and younger populations, they tend to result from trauma, multiple subluxations, or repetitive overhead motions where large rotational torques are observed, often occurring in athletes participating in sports such as baseball, tennis, or swimming.…”
Section: Introductionmentioning
confidence: 99%
“…7 Although RC injuries are a common etiology for shoulder pain in adults, evidence suggests RC lesions occur less often in the pediatric population, and account for less than 1% of all total RC tears. 2,14 Current literature reports shoulder injuries comprise nearly 11% of all high school athlete injuries 15 . However, few studies have reported the incidence of RC tears in the pediatric population, with current evidence limited to case reports and small retrospective reviews.…”
Section: Introductionmentioning
confidence: 99%